ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS LAPORAN KEUANGAN PEMERINTAH KABUPATEN BOLAANG MONGONDOW - Pieter Roya; Herman Karamoy; Hendrik Gamaliel (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2023)
The objective of research was to discover and analyze the factors that influence the financial statement quality of Bolaang Mongondow regency. The independent variables consisted of the implementation of SAP (Government Accounting Standard), the implementation of SAKD (Regional Financial Accounting System), competency of human resources, environment control, and compliance with laws and regulations. The population of the research was 48 OPD (Regional Government Organizations) in Bolaang Mongondow regency and the sample was taken by applying a saturated sampling technique. This research distributed 240 questionnaires to Budget users/Proxy of Budget Users, Commitment-making Officers, Finance Administration Officers, revenue and expenditure treasurers, and Financial Statement Prepares at OPD in Bolaang Mongondow. The data were analyze by using multiple linear regression analysis. The result demonstrated that the implementation of SAP, use of SAKD, competency of human resources, and control environment had a significantly positive influence on the financial statement quality. Compliance with laws and regulations had insignificantly positive influence on the financial statement quality of Bolaang Mongondow regency.